Association of face mask use with self-reported cardiovascular symptoms during the COVID-19 pandemic - Nicholas Wen Sheng Chew; Raymond Ching Chiew Wong; Andie Hartanto Djohan; Jinghao Nicholas Ngiam; Ping Chai; Tiong-Cheng Yeo; Huay-Cheem Tan; Ching-Hui Sia (Singapore Medical Journal)
Introduction: Countries are mandating the use of face masks to stem the spread of coronavirus disease 2019 (COVID-19). Face mask use has been associated with discomfort due to its effects on thermoregulation, breathing and oxygenation. We evaluated the prevalence and severity of self-reported cardiovascular symptoms before and during face mask use. Methods: This was a cross-sectional study of 1,001 participants residing in Singapore, who participated in a self-administered questionnaire between 25 April 2020 and 4 May 2020. Symptom severity before and during mask use, and health-seeking behaviour information were collected. The study outcome was self-reported worsening of cardiovascular symptoms and its association with the type of mask worn, duration of mask worn per day, and intensity of physical activities during mask use. Results: The most common symptom reported during mask use was dyspnoea. Independent predictors for self-reported cardiovascular symptoms during mask use were moderate–high physical activity during mask use (odds ratio [OR] 1.634, 95% confidence interval [CI] 1.176–2.270, P = 0.003), duration of mask use for ≥3 h (OR 1.672, 95% CI 1.189–2.352, P = 0.003) and type of mask used, after adjusting for age, sex, healthcare-based worker status and presence of comorbidities. N95 mask was associated with worse symptoms when compared to surgical mask. Participants with ≥3 worsening symptoms or worsening dyspnoea, palpitations, fatigue and dizziness were more likely to seek medical help. Conclusion: Face mask use has been proven to be an effective way in curbing COVID-19 transmission. However, participants in this study had concerns regarding its use and these concerns should be urgently addressed to enable mask use policies to be enacted.